THE PURPOSE OF EDUCATION IN THE PERSPECTIVE OF THE QUR'AN: (Study of Analysis of the interpretation of Surah Ali Imron Verses 138-139) - Halil , Hermanto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
The objectives of Islamic education have a very broad scope both materially and spiritually. Islamic education does not only see education as an effort to educate but is in line with the Islamic concept of man and the nature of his existence. In fact, Islamic education seeks to foster an understanding and awareness that humans are equal in front of Allah, the difference is the level of devotion as a form of qualitative difference. Finally, the goal of Islamic education is to produce human beings who are faithful and knowledgeable, and support each other. Otherwise, it can be declared as a new ignorance. Keywords: Purpose of Education, Quranic Perspective